Approaching Today S Cultural Fabric: Krenak - Pizarro-Romero, A (UNIV FEDERAL FLUMINENSE, 2024)
The text wants to get closer to the moving fabric that forms culture and for this it refers to the systems that build it. One of them is that of indigenous cultures. This thought, according to Ailton Krenak, considers a reality where the human is only part of a world that silences other presences. Today the existence of this other previously discriminated form of thought is beginning to be recognized. It is necessary to accept that there are different valid forms of relationship with the world, beyond that of the West, which is what we know and gives rise to our form of modernity. Krenak confronts the anthropocentric conception. The West does not listen. Bruno Latour s thought, however, is in the previous line, promoting the non-separation between nature and culture. Community that is transcendence. It is the one offered by literature and art. It is necessary to listen to the stories of this other worldview.